The art of combining between a text of Nali's poetry and Abdullah ibn Hamam al-Sululi - ئیسماعیل, د. زاهیر ئیسماعیل سەعید (Sulaimani Journal for Humanities, 2025)
This discussion is a comparative analysis research between one of the text (nali)’s poem on Baban time and Arabic poet (Abdalla Hamam bn alsluli) on Umayyad era this comparison was done under the light French comparative school, because Arabic literature had an effect on Kurdish literature in terms of history and more attention on psychology art of collection in this comparative that is a type semantic aesthetic psychological ates that used to beauty a text of Arabic poetry and the history of this art has gone back to pre Islamic time . The purpose of this art is for the poet to combine two contradictory meanings to convey two different messages in one text, for example sympathy and congratulations. In this two texts. We were comparing. It appeared for us Which had a lot of similar phenomenons between them. these similarities appeared In art and message of poetry, the text of Abullh’s poem for the death of (mhawiya) the caliph of the Umayyads and took over the caliphate by ( yazid) his son that was written by the some way, the text of (nali)s poem for the death of (sleman pasha) Emir of Baban and took over the Emir by (ahmad pasha) his son. Both texts and poet’s were written for sympathy and congratulation for caliph and the new Emie, at the same time messages of islam religion in the text of the poems for describing their personalites were appeared clearly.
Keywords: Comparative literature; collection art; Contradiction; sympathy and congratulate; sleman pasha Baban; ahmad pash; mhawiya; yazid